Evaluasi Bangunan Pelindung Pantai Sisi Miring Dalam Upaya Penanggulangan Abrasi Pesisir Pantai - Akmal, Akmal; Putra, Sahri (University of Muhammadiyah Aceh, 2021)
The coast of Kampung Jawa Lama, Banda Sakti Sub-district, Lhokseumawe City is a fishing area and densely populated. The breakwater building in the coastal area of Kampung Jawa Lama is a sloping Breakwater with a height of 1.5 m and a width of 1 m. The type of breakwater used is usually determinet by the availability of material on the site. The problem in this research was the cause of abrasion and its impact, as well as how to plant coastal protection structures. The purpose of this study was to reduce the impact of erosion, abrasion and damage to the buildings and to re-evaluate coastal structures. The method used on this research is Hudson method and descriptive analysis by making direct observation and reviuwing research that has been done previously. The cause of abrasion is triggered by several factors such us tides, high sea waves and ocean currents that have the potential to cause damage as a result of strong winds that produce destructive waves. The community also receiver the impact of the abrasion, namely decreasing income, the place where they live is inundated by sea water and it affects the decline in the quality of life of the community. One of the efforts that can be applied to reduce the abrasion problem in the area is to build a Breakwater construction. Based on calculation, the results obtained in the planning reviuw of the existing shoreline protection building were 1.5 m, so that to prevent abrasion the increase in height of the building 4.074 m was 5.574 m with a peak width of 1 m so that increase of 0.20 m was 1.2 m, the thickness of the first layer of protection was 1.2 m and the thickness of the second layer was 0.60 m. The width of the leg guard is 1.8 m with a thickness of 0.5 m